Three-dimensional iron(ii) porous coordination polymer exhibiting carbon dioxide-dependent spin crossover. Issue 34 (26th March 2018) - Shin, Jong Won; Jeong, Ah Rim; Jeoung, Sungeun; Moon, Hoi Ri; Komatsumaru, Yuki; Hayami, Shinya; Moon, Dohyun; Min, Kil Sik
Abstract : A three-dimensional iron(ii ) porous coordination polymer has been observed spin crossover behaviours through the sorption of H2 O and CO2, respectively. Abstract : We report a three-dimensional Fe(ii ) porous coordination polymer that exhibits a spin crossover temperature change following CO2 sorption (though not N2 sorption). Furthermore, single crystals of the desolvated polymer with CO2 molecules at three different temperatures were characterised by X-ray crystallography.